At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

5(−2) + (2−)2
when =3 and =−2


Sagot :

Answer:

36 is the final value for the equation you posted

Step-by-step explanation:

We are told that = 3 and = −2.

Let's plug these values into the equation.

= (5 ( − 2) + (2 − )^2)

= (5 (3 − 2(−2)) + (2 − 3)^2)

= (5 (3 + 4) + (−1)^2)

= (5 (7) + 1)

= 35 + 1

= 36